2014
DOI: 10.1094/phyto-12-12-0334-r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantification of Fungal Colonization of Phakopsora pachyrhizi in Soybean Genotypes

Abstract: Soybean rust, caused by the fungus Phakopsora pachyrhizi, is an economically important disease of soybean with potential to cause severe epidemics resulting in significant yield losses. Host resistance is one of the management tools to control this disease. This study compared soybean genotypes exhibiting immunity, complete and incomplete resistance, and susceptibility to an isolate of P. pachyrhizi based on visual assessment of reaction type, other visual traits such as sporulation, quantitative measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…In the case of P. gossypii at 42 hai the uredospores germinated, produced a germ tube and an appressorium that might directly allow the fungus to penetrate the leaf cuticle ( Figure 1A). According to Vittal et al (2014), the early events of uredospore germination, appressorium formation, and penetration of P. pachyrhizi on the soybean leaf occurred by 24 hai. The formation of appressoria is a pivotal event that allows a number of fungi to penetrate the leaf cuticle and establish a successful infection in their hosts (Chang et al, 2014;Dean, 1997;Loehrer et al, 2014;Ludwig et al, 2014;Mendgen and Deising, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of P. gossypii at 42 hai the uredospores germinated, produced a germ tube and an appressorium that might directly allow the fungus to penetrate the leaf cuticle ( Figure 1A). According to Vittal et al (2014), the early events of uredospore germination, appressorium formation, and penetration of P. pachyrhizi on the soybean leaf occurred by 24 hai. The formation of appressoria is a pivotal event that allows a number of fungi to penetrate the leaf cuticle and establish a successful infection in their hosts (Chang et al, 2014;Dean, 1997;Loehrer et al, 2014;Ludwig et al, 2014;Mendgen and Deising, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Medice et al (2007) reported that the uredia of P. pachyrhizi on soybean leaves became completely open at 36 dai. Generally, the small and closed uredia of P. pachyrhizi on soybean leaves were associated with reduced Asian soybean rust symptoms because they produced fewer uredospores (Cruz et al, 2012;Medice et al, 2007;Vittal et al, 2014). The results from the present study strongly indicate that control managements against tropical rust, such as fungicides should be implemented up to a maximum of 20 days after the infection took place because from this time onwards, the uredia start to open and release the first uredospores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An appressorial cone initiates the penetration into the epidermal cell by turgor pressure independent of melanin accumulation (Chang et al 2014). Penetration hyphae grow through the epidermal cell and intercellular space, first forming primary invading hyphae, then secondary hyphae populating intercellular spaces (Bonde et al 1976;Edwards and Bonde 2011;Koch et al 1983;Vittal et al 2014). In compatible interactions, primary haustoria form in the mesophyll cells, secondary haustoria form within 12 days, and a domed-shaped eruption occurs in the epidermis to form uredinia that often have a rusty appearance on infected leaves of both kudzu and soybean (Fig.…”
Section: Classification Infection Host Range and Virulencementioning
confidence: 99%
“…In an incompatible interaction, branching of fungal hyphae in the mesophyll is not common, and is associated with mesophyll cell necrosis (McLean 1979). During the 24 h after inoculation, spore germination, appressorium formation, and fungal penetration of the epidermis in susceptible and resistant soybean genotypes are similar but, within 2 days, more hyphae occur in the mesophyll tissue of susceptible than in resistant genotypes, and mesophyll cell death is greater in soybean genotype with an immune response, demonstrating that an incompatible soybean-P. pachyrhizi interaction restricts hyphal development in the mesophyll cell tissue (Vittal et al 2014). A very similar response was observed in kudzu as well, where the resistant interactions had early onset of a multicell hypersensitive response, while immune interactions were the result of a cell wall deposition that blocked penetration in combination with early onset of a hypersensitive response (Jordan et al 2010) (Fig.…”
Section: Classification Infection Host Range and Virulencementioning
confidence: 99%